2013
DOI: 10.1111/febs.12478
|View full text |Cite
|
Sign up to set email alerts
|

Dose‐dependent inhibitory effects of proton pump inhibitors on human osteoclastic and osteoblastic cell activity

Abstract: Proton pump inhibitors (PPIs), a class of molecules that are used to decrease gastric acid production, might have adverse effects on bone metabolism. The aim of this study was to characterize the concentration-dependent and time-dependent effects of three PPIs (omeprazole, esomeprazole, and lansoprazole) on human osteoclast precursor cells isolated from peripheral blood, and on human mesenchymal stem cells (osteoblast precursors). Cell cultures were characterized for total protein content, apoptosis, and sever… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
62
1
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(72 citation statements)
references
References 49 publications
(85 reference statements)
3
62
1
3
Order By: Relevance
“…A fall in the blood calcium concentration not only affects bone formation, which is regulated by osteoblasts, but also promotes bone resorption by osteoclasts, followed by a decrease in bone mineral density [81, 82]. Second, PPIs could inhibit the V-ATPase of osteoclasts in the same way that PPIs inhibit gastric H + /K + -ATPase, having a direct deleterious effect on bone cells, with the possibility of decreased bone turnover [83]. Third, long-term use of PPIs could cause a homocysteine concentration and parathyroid hormone increase, which interfere with collagen cross-linking and weaken bone [82].…”
Section: Some Potential Adverse Effects Of Ppismentioning
confidence: 99%
“…A fall in the blood calcium concentration not only affects bone formation, which is regulated by osteoblasts, but also promotes bone resorption by osteoclasts, followed by a decrease in bone mineral density [81, 82]. Second, PPIs could inhibit the V-ATPase of osteoclasts in the same way that PPIs inhibit gastric H + /K + -ATPase, having a direct deleterious effect on bone cells, with the possibility of decreased bone turnover [83]. Third, long-term use of PPIs could cause a homocysteine concentration and parathyroid hormone increase, which interfere with collagen cross-linking and weaken bone [82].…”
Section: Some Potential Adverse Effects Of Ppismentioning
confidence: 99%
“…Studies have explored the potential effects of PPIs on calcium absorption 40 , bone mineral density (BMD) 4144 , bone metabolism 45, 46 , increased histamine release 47 , or their association with fall risk 16, 23 . In addition, it has been hypothesized that PPI use may be associated with hyperparathyroidism 48 , which has been recently reported in a cohort of elderly subjects 49 .…”
Section: Discussionmentioning
confidence: 99%
“…Efficient calcium absorption is an important determinant of long‐term skeletal integrity. PPI‐induced hypochlorhydria can decrease calcium absorption in elderly adults, who are less able to upregulate calcium absorption from the intestines . However, no studies have found an association between long‐term PPI exposure and low bone mineral density (BMD) or a decrease in BMD over time .…”
Section: Discussionmentioning
confidence: 99%
“…Data supporting any underlying disease mechanism(s) caused by PPIs and their effects on common laboratory parameters are limited . Increasing evidence suggests that PPIs may disrupt skeletal integrity through two primary and potentially synergistic mechanisms: PPI‐induced hypochlorhydria impairs calcium absorption and reduces calcium bioavailability for incorporation into bone, resulting in compensatory and potentially chronic hyperparathyroidism, which increases bone turnover; and PPIs can directly inhibit acid‐dependent osteoclasts and impair adequate bone resorption, which results in dense but fragile bones …”
mentioning
confidence: 99%